Competing approaches to forecasting elections: economic models, opinion polling and prediction markets - Andrew Leigh; Justin Wolfers (Institute for the Study of Labor (IZA), 2006)
We review the efficacy of three approaches to forecasting elections: econometric models that project outcomes on the basis of the state of the economy; public opinion polls; and election betting (prediction markets). We assess the efficacy of each in light of the 2004 Australian election. This election is particularly interesting both because of innovations in each forecasting technology, and also because the increased majority achieved by the Coalition surprised most pundits. While the evidence for economic voting has historically been weak for Australia, the 2004 election suggests an increasingly important role for these models. The performance of polls was quite uneven, and predictions both across pollsters, and through time, vary too much to be particularly useful. Betting markets provide an interesting contrast, and a slew of data from various betting agencies suggests a more reasonable degree of volatility, and useful forecasting performance both throughout the election cycle and across individual electorates.
Keywords: D72; D84; 330; voting; elections; prediction markets; opinion polling; macroeconomic voting; Prognoseverfahren; Wirtschaftsprognose; Meinungsforschung; Öffentliche Meinung; Glücksspiel; Wahl; Australien